143k views
5 votes
Factor 4x2 + 12x + 8.

User Xcross
by
5.7k points

2 Answers

5 votes

Answer:

The answer is 4(x+1)(x+2).

Explanation:

First, you have to simplify the expression by taking out the common terms :


4 {x}^(2) + 12x + 8


= 4( {x}^(2) + 3x + 2)

Next, you have to factorize it by elaborating :


4( {x}^(2) + 3x + 2)


= 4( {x}^(2) + x + 2x + 2)


= 4(x(x + 1) + 2(x + 1))


= 4(x + 1)(x + 2)

User Hollyann
by
5.2k points
1 vote

Answer:

4(X+2)(X+1)

solution,


4 {x}^(2) + 12x + 8 \\ = 4( {x}^(2) + 3x + 2) \\ = 4( {x}^(2) + (2 + 1)x + 2) \\ = 4( {x}^(2) + 2x + x + 2) \\ = 4(x(x + 2) + 1(x + 2) \\ = 4(x + 2)(x + 1)

User Wawek
by
5.8k points